The Description of Family Knowledge About How To Prevent The Occurrence of Psychosocial Disorders During The Pandemic Covid-19 - Sulistyorini, Ariani; Anwar, Muhammat Lutfi Nuril (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: The Covid-19 is an infectious disease caused by coronavirus infection. During the Covid-19 pandemic can cause psychosocial disorders such as stress, anxiety, and depression. One of the ways that determines the success of families in preventing psychosocial disorders during the Covid-19 pandemic is to know how to do 5B activities (learning, worship, playing, chatting and recreation together), increasing physical immunity, as well as improving mental and psychosocial health such as positive emotions, positive thoughts, positive social relationships.Purpose: This study aimed to know the overview of family knowledge on how to prevent psychosocial disorders during the Covid-19 pandemic.Methods: This research used a descriptive crossectional design with a population of 318 families and a large sample of 39 families, sampling was done by Random Sampling method. The research variable is an overview of family knowledge on how to prevent psychosocial disorders during the Covid-19 pandemic. Data collection was held on 15 – 30 December 2020. The research instrument used in data retrieval is a questionnaire. The collected data is then analyzed with the help of frequency distribution tables.Results: From the results of the study obtained from 39 respondents, 18 respondents (46%) good knowledge, 16 respondents (41%) enough knowledge and 5 respondents (13%) lees of knowledge on how to prevent psychosocial disorders during the Covid-19 pandemic.This is due to factors that influence knowledge, age, education, employment, never/unable to get information about the prevention of psychosocial disorders during the Covid-19 pandemic.Conclusion: To increase family knowledge of enough and less categories, respondents are expected to add and search for information through health workers as well as media such as TV, Internet, and newspapers. Respondents with good knowledge should apply in their daily lives and help health workers socialize on how to prevent psychosocial disorders during the covid-19 pandemic to other families